Group Dynamics and Student Participation in a Chinese Setting: Teacher and Observer Perspectives - John Harper; Hui-ju Chen (Journal of English Language Teaching and Linguistics, 2018)
This article addresses the frequently discussed notion of Chinese students’ supposed reticence and passivity in the English as a Foreign Language classroom. Using the concept of group dynamics as a starting point, it examines teachers’ classroom-management techniques in terms of promoting (or not promoting) active student participation. The study, using a grounded theory of research, analyzed classroom data obtained from class observations and from class filmings and supplemented these data with post-lesson interviews with the four involved teachers. Findings suggested that Chinese students were not necessarily reticent or passive but rather engaged actively when given a learning environment conducive to active engagement. The study pointed to three practical implications for classroom teachers: (1) promoting participation by working toward group cohesion, (2) promoting participation by providing effective teacher-student scaffolding and by providing opportunities for student-student scaffolding, (3) promoting participation by actively replacing textbook materials in order more effectively to offer students adequate support in terms of both language and affect. Acknowledging the fact that different institutional contexts may require different classroom-management techniques, the study calls for further testing of the present findings in other Chinese settings.